(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This research paper attempts to examine how reading books help for healing trauma of victim in Markus Zusak’s The Book Thief. Liesel Meminger, the protagonist gains rational power from her learning of reading books that Hans taught when she started stealing books from grave yard and the markets. Indeed, this study highlights that her habit of passionate reading of books in the war period heals her psychological disorder by forgetting her past. Relying on the concepts of Dominic LaCapra’s "Writing History, Writing Trauma", Cathy Caruth’s "trauma as a wound”, Herman’s “the role of memory and narrative in the healing process”, and Tedeschi and Calhoun’s “posttraumatic growth”, this paper gives emphasis to that Liesel gets healing from trauma through the process of reading that she ables to express her experience of witnessing. Furthermore, this study offers an ample examination of how reading becomes a vital tool for healing in the visage of adversity by delving into the intricate interplay between trauma, text, and toughness. Therefore, it can be concluded that reading can heal trauma however, it is difficult to root out that why the glimpses of memories can be seen inside the mind.